The effect of oral glucose administration before surgery based on Enhanced Recovery After Surgery (ERAS) protocol on preventing insulin resistance and patient's quality of life - Jufriady Ismy; Indra Wisesa; Muhammad Yusuf; Iflan Naufal; Imam Hidayat; Muslim (Journal of International Surgery and Clinical Medicine, 2021)
Introduction Preoperative oral glucose administration is part of the ERAS protocol, which is still not implemented worldwide. This study aims to determine the effect of preoperative oral glucose administration based on the ERAS protocol on the patient's quality of life and insulin resistance. Method This study is a quantitative quasi-experimental study (post-test with control group) involving patients undergoing surgery using general anesthesia at dr. Zainoel Abidin Banda Aceh from January 2021 to April 2021. The intervention was carried out on patients who were about to undergo surgery divided into two groups: the group receiving and the group not receiving 50 grams of oral glucose 2 hours before surgery according to the ERAS protocol. The data obtained were processed using Chi Square statistical test, Mann- Whitney, and unpaired T-test to assess patients' quality of life and insulin resistance. Result A total of 48 patients (24 treatment group and 24 control group patients) were involved in the study. There were significant mean differences in all quality of life indicators between the group receiving and the group not receiving oral glucose with a significance value of p<0.05. There is a relationship between oral glucose administration and prevention of insulin resistance with a significance value of p<0.05. Conclusion: There is a relationship between preoperative oral glucose administration on quality of life and postoperative insulin resistance according to the ERAS protocol.